The impact of Israel's Front-of-Package labeling reform on consumers' behavior and intentions to change dietary habits - Shosh Shahrabani (BMC, 2021)
Abstract Background In January 2020, Israel launched a reform mandating Front-of-Package (FOP) labeling on food products. The current study examined the factors affecting consumers' decision-making regarding the use of FOP labels a year after the reform was implemented. Methods The survey was conducted between December 2020 and January 2021 and included a sample of 507 participants age 21 and over. The questionnaire included Health Belief Model (HBM) constructs related to food labeling, nutrition habits, media exposure and extent of support for the reform, frequency of using FOP labels, intention to change purchasing and consumption habits in the coming year, and personal details. Results The study found that 58.5% reported using the FOP labels to some extent. In addition, 70% indicated willingness to change to healthier products in the coming year. The results of the analytical model confirm the validity of the HBM and the other behavioral constructs. In particular, the frequency of using FOP labels increases as the following factors increase: levels of perceived benefits and perceived importance of reading FOP labels, level of perceived importance of healthy nutrition, frequency of conforming to healthy nutrition, and support for the reform. Conclusions The study's findings are important for understanding the impact of the new reform and for guiding future complementary actions to increase people's motivation to use FOP labels. More advertisement about the FOP labels in the media and also through the HMOs is needed to increase people's awareness of the reform. In addition, information about the reform provided to the public should emphasize the benefits and health implications of using FOP labels.